2008
DOI: 10.1108/14691930810913177
|View full text |Cite
|
Sign up to set email alerts
|

The evolving research on intellectual capital

Abstract: This paper reviews the literature pertaining to developments in the field of Intellectual Capital (IC). Four areas are examined: definitions, models, measures and applications of IC to business and management issues. As an emerging field of study, IC has undergone a number of development stages. The first stage witnessed efforts to raise awareness of the importance and potential of IC. The second saw a consolidation of the concept that established research into IC as a legitimate undertaking. A subsequent stag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(27 citation statements)
references
References 42 publications
0
26
0
1
Order By: Relevance
“…Institutions are pivotal in creating the appropriate environment to support markets and market transactions, which, subsequently, sustain the NSI. However, the study of NSI for policy purposes is challenging for the following reasons: uncertainty and the complex adaptive system (CAS) nature of NSI (Holland 2006;Lane and Maxfield 2004); the problematic of modularity i.e. the selection of unit(s) of analysis; and evolution in terms of capturing the state of NSI when it is most stable and representative.…”
Section: Introductionmentioning
confidence: 99%
“…Institutions are pivotal in creating the appropriate environment to support markets and market transactions, which, subsequently, sustain the NSI. However, the study of NSI for policy purposes is challenging for the following reasons: uncertainty and the complex adaptive system (CAS) nature of NSI (Holland 2006;Lane and Maxfield 2004); the problematic of modularity i.e. the selection of unit(s) of analysis; and evolution in terms of capturing the state of NSI when it is most stable and representative.…”
Section: Introductionmentioning
confidence: 99%
“…As ROA and MCM primarily build on this type of measure they are suited to integration with engineering design performance measurement frameworks at higher organisational levels, where dynamic individual/team behaviour is less directly influential (Tan, Plowman, and Hancock 2008). Thus they leave a significant gap at lower levels and in the management of dynamic intangible aspects, particularly with respect to engineering design processes.…”
Section: Performance Indicator Inflation: Measuring and Monitoring Mamentioning
confidence: 99%
“…The growing importance of intangible assets in the last two decades has stimulated a wealth of studies on this topic, leading some researchers to enquire about the state of art and the future trends of this research field Pew Tan et al 2008;Guthrie et al 2012;Edvinsson, 2013;Dumay, 2014;2016). Within this article, we only briefly examine the main stages of IC research as identified by Guthrie et al (2012).…”
Section: Research Framework and Literature Reviewmentioning
confidence: 99%